INTRATHECAL DEXMEDETOMIDINE-FENTANYL FOR LABOR ANALGESIA: A COMPARATIVE PROSPECTIVE STUDY - Chopade , Nitin P (Journal of Biomedical and Pharmaceutical Research, 2020)
BACKGROUND: Women have reported the agony they experience during childbirth as being severe and frequent, and they often have few or no choices for pain management, particularly in developing nations. In many low resource settings, sedatives and parenteral opioids are the most often recommended medications for women in labor. It has been demonstrated that his approach to pain treatment has little to no impact on labor discomfort. One of the main aims of maternity care is to relieve pain during labor. Combining spinal and epidural analgesia is a well-known method for reducing labor pain with no risk to the mother or fetus. Dexmedetomidine has been used intrathecally with bupivacaine for prolonged postoperative analgesia. It is a highly selective alpha 2 adrenoreceptor agonist with analgesic effects. It is highly lipophilic and barely crosses the placenta, according to recent evaluations. AIM: The study’s objective was to compare the effects of intrathecal dexmedetomidine and fentanyl to those of either drug alone on mother and newborn outcomes during labor. MATERIAL AND METHOD: The department of anesthesia conducted this comparative prospective observational study. All participants gave their informed and written agreement to be included in the study and to have their data used for the current research project. 100 pregnant women who were full term and admitted to the obstetric department for safe confinement made up the participants. The study was conducted in a designated labor room of the obstetrics division of a teaching hospital with tertiary care. A multipara monitor, ultrasound, anesthetic workstation, and resuscitation supplies are available in the delivery room. The pregnant moms have described the benefits and process of labor analgesia. For every patient to be included in the trial, the approval of an obstetrician was required. RESULTS: 120 parturient in all met the inclusion requirements, 110 of them gave their consent and were subsequently recruited in the study after the inclusion criteria were applied. According to the exclusion criteria, ten patients were disqualified. once the predetermined sample size of 100 patients has been reached. The study of the block quality showed that Group A experienced analgesia sooner than Group B. Statistics showed that the differences were substantial. In Group A, the analgesia lasted longer as well. According to the examination of motor block, Group A has more motor block than Group B has. According to the analysis of side effects, pruritus, hypotension, bradycardia, shivering, and nausea were the most frequent side effects. CONCLUSION: Contrary to dexmedetomidine or fentanyl used alone, intrathecal dexmedetomidine prolongs the duration of analgesia and reduces the prevalence of side effects. A secure and reliable technique for labor analgesia is the use of an intrathecal adjuvant walking epidural. With intrathecal dexmedetomidine, the block’s intensity and duration are greater. The likelihood of a normal vaginal birth is increased with fentanyl. Dexmedetomidine should not be used as an intrathecal adjuvant for labor analgesia; fentanyl should. Compared to fentanyl, it offers an acceptable level of labor analgesia with a longer analgesic duration. KEYWORDS: Analgesia, Dexmedetomidine, Fentanyl, Labor, Neonatal and labor analgesia